2007
DOI: 10.1177/0010414006286542
|View full text |Cite
|
Sign up to set email alerts
|

The Varieties of Capitalism and Hybrid Success

Abstract: for comments on a previous draft. Peer Hull Kristensen provided especially helpful suggestions about the Danish vocational training system. This research was funded in part by the Danish Funktionaerernes og Tjenestemaendenes Faellesråd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(81 citation statements)
references
References 47 publications
1
74
0
6
Order By: Relevance
“…Notably, the literature on production regimes, which provided us with the concepts of liberal and coordinated market economies, has been criticized for being overly simplistic and neglecting the proliferation of hybrid forms (Campbell and Pedersen 2007;Crouch 2005). As a result, there may be important differences in production, policy-making, and, therefore, knowledge regimes among countries that fall into any of the four political economic types we have discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the literature on production regimes, which provided us with the concepts of liberal and coordinated market economies, has been criticized for being overly simplistic and neglecting the proliferation of hybrid forms (Campbell and Pedersen 2007;Crouch 2005). As a result, there may be important differences in production, policy-making, and, therefore, knowledge regimes among countries that fall into any of the four political economic types we have discussed.…”
Section: Discussionmentioning
confidence: 99%
“…While bricolage refers to the recombination of already existing repertoires and elements, translation refers to the spread of new ideas and practices from one setting to another (Campbell 2007). However, the introduction and adoption of new ideas does not take place in wholesale fashion and instead needs to be translated to the local context, in order to fit with already existing institutional arrangements.…”
Section: Maria Luisa Mendes Teixera Poliano Bastos Da Cruz and Elisementioning
confidence: 99%
“…Other research has shown how neoliberal policy ideas have similarly been adapted to local context. In Denmark, for example, the import of neoliberal ideas led to a greater marketization in some spheres of the economy, while maintaining cooperative relationships between different stakeholders in other spheres (Campbell and Pedersen 2007).…”
Section: Maria Luisa Mendes Teixera Poliano Bastos Da Cruz and Elisementioning
confidence: 99%
“…1 The major welfare state reforms, active labor market, and social policies were viewed as a profound deviation from the past: the object was to move the unemployed into compulsory jobs and training programs, and observers interpreted this as a move toward liberalism (Campbell and Pedersen, 2007). A leader in "decommodification," Denmark was suddenly at the forefront of efforts to recommodify the unemployed (and potentially strip citizens of their social rights by taking away unconditional legal claims to support) (Abrahamson, 1998).…”
Section: Business Coordination Social Protections and Equalitymentioning
confidence: 99%